Efektivitas Penggunaan Model Pembelajaran Project Based Learning Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran Teknik Frais Di SMK Negeri 1 Tanjung Raya - Putra Fajar Perdana; Fiki Efendi; Budi Syahri; Febri Prasetya (Unversitas Negeri Padang, 2025)
The low learning results of students when learning the Frais Technique serve as the impetus for this study. It is believed that this is because students are not actively participating in teacher-centered learning models and their learning is not at its best. The purpose of this study is to ascertain how well the Project Based Learning learning paradigm affects the learning outcomes of SMK Negeri 1 Tanjung Raya students studying framing techniques. This study employs quantitative approaches and quasi-experimental research. 40 students made up the study's sample, and they were divided into two categories: the experimental category and the control category. The research period was carried out during the academic year 2024–2025's odd semester. The findings from the analysis of the data in this research suggest that the learning model centered around projects is significantly more influential than the conventional model to improve learning outcomes, the findings of the analysis illustrate that the average post-test results of the experimental class of 75.25 are greater than the control class with an average of 63.75. Based on the results of research and discussion, quasi-experimental research on the XI grade Frais Engineering Subject at SMK Negeri 1 Tanjung Raya can be concluded that there is an effectiveness of using project-based learning models on student learning outcomes where the value of learning outcomes in groups using project-based learning models is higher than conventional models.